Design and Implementation of a Perioperative Surgical Home at a Veterans Affairs Hospital. (June 2016) - Walters, Tessa L.; Howard, Steven K.; Kou, Alex; Bertaccini, Edward J.; Harrison, T. Kyle; Kim, T. Edward; Shafer, Audrey; Brun, Carlos; Funck, Natasha; Siegel, Lawrence C.; Stary, Erica; Mariano, Edward R.
The innovative Perioperative Surgical Home model aims to optimize the outcomes of surgical patients by leveraging the expertise and leadership of physician anesthesiologists, but there is a paucity of practical examples to follow. Veterans Affairs health care, the largest integrated system in the United States, may be the ideal environment in which to explore this model. We present our experience implementing Perioperative Surgical Home at one tertiary care university-affiliated Veterans Affairs hospital. This process involved initiating consistent postoperative patient follow-up beyond the postanesthesia care unit, a focus on improving in-hospital acute pain management, creation of an accessible database to track outcomes, developing new clinical pathways, and recruiting additional staff. Today, our Perioperative Surgical Home facilitates communication between various services involved in the care of surgical patients, monitoring of patient outcomes, and continuous process improvement.